Characterization of silicon ingots: Mono-like versus high-performance multicrystalline. (9th July 2015) - Kutsukake, Kentaro; Deura, Momoko; Ohno, Yutaka; Yonenaga, Ichiro
Abstract: Mono-like Si and high-performance multicrystalline Si ingots were grown using the same furnace and the same procedure for growth, but different seeds. In addition, a conventional multicrystalline Si ingot was grown using the same furnace, by a different growth procedure. By comparing the grain structures, the distribution of carrier lifetime, and dislocations in the ingots, we qualitatively illustrated their material features. The average carrier lifetime of the mono-like Si is almost the same as that of the high-performance multicrystalline Si, and slightly shorter than that of the conventional multicrystalline Si. This would be caused by the higher density of metal contaminants owing to the longer process time for raw material melting. The density of dislocations and their clusters was significantly lower in the mono-like Si and high-performance multicrystalline Si than that in the conventional multicrystalline Si. The origin of these differences was discussed on the basis of the difference in the growth procedure and grain structure of the ingots.